The Spirit and the meal as a model for Charismatic worship: A practical-theological exploration - Denny, Lindie; Wepener, Cas (Hervormde teologiese studies, 2013)
The purpose of this article is to present one aspect of a larger research project. The Spirit tradition (Charismatic) and its liturgical rituals as well as the Meal tradition (Liturgical Movement) and its liturgical rituals through history were researched as well as the concomitant theology. The aim was to gain a better understanding of whether the future of Charismatic worship can benefit from a somewhat closer integration of aspects of the meal tradition, especially the celebration of the Lord’s Supper. This article will mostly be focused on the empirical research done in this project within three Charismatic churches in Gauteng, South Africa. This research seeks to contribute to Robert Webber’s model of bringing old and new together in synergy. In the end, this article poses a new model for Charismatic worship when liturgical-rituals of the Spirit are combined with the celebration of communion in a way that worshippers experience as being more meaningful.